Pancreatic Lipomas – Prevalence in Patients Undergoing Abdominal CT - Gossner, Johannes (International Scientific Literature, Inc., 2014)
BACKGROUND: Pancreatic lipomas are reported to be rare but their prevalence is unknown. This study examined the prevalence of pancreatic lipomas in a sample of patients undergoing abdominal computed tomography. MATERIAL/METHODS: Retrospective review of 100 abdominal computed tomographic scans. RESULTS: In 6 patients small pancreatic lipomas were found. There was no predominance in location or gender. The lipomas measured between 4 and 12 mm. All lipomas were incidental findings unrelated to patients’ symptoms. CONCLUSIONS: Pancreatic lipomas seem to be quite a common finding and can be found in 6% of patients undergoing abdominal CT. Radiologists should be aware of this finding to establish proper differential diagnosis.